1999
DOI: 10.1046/j.1365-2168.1999.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of a surgical high-dependency unit

Abstract: Postoperative management on an HDU was associated with fewer cardiorespiratory complications. There was no difference in mortality rate but there was a trend towards shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 9 publications
1
31
0
1
Order By: Relevance
“…The allocation of patients to the ICU or HDU currently depends on comorbid conditions, operative complexity and the surgeon's or anaesthetist's subjective assessment of a patient after surgery. Guidelines on admission to and discharge from the HDU or ICU have been issued by the UK Department of Health 3 , and the value of HDU care has been extensively reviewed in the literature 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The allocation of patients to the ICU or HDU currently depends on comorbid conditions, operative complexity and the surgeon's or anaesthetist's subjective assessment of a patient after surgery. Guidelines on admission to and discharge from the HDU or ICU have been issued by the UK Department of Health 3 , and the value of HDU care has been extensively reviewed in the literature 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In Table 2 , Jones et al . 18 prospectively compared the outcomes of patients undergoing major abdominal surgery in a hospital with an HDU to a hospital without an HDU. Table 3 details a retrospective versus prospective audit by Kapur et al.…”
Section: Resultsmentioning
confidence: 99%
“…(17) A supplementary classification is proposed in order to identify those patients requiring specialist investigation and treatment such as is usually provided at tertiary referral hospitals. Where patients are cared for by specialist services, one additional letter (reflecting the most significant disorder) should be applied to a patient's level of acuity as follows: (18) The extent to which any individual hospital provides increasing levels of care, or supplementary specialist care, depends on the skills, expertise, specialties and facilities available in the hospital. Services provided should be based on the principle of moving upwards from level 0, to the level that is appropriate to the complexity of patient care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, without higher levels of nursing care and monitoring, other studies have reported higher complication rates and lengths of stay as a result. 31 Observation of the WR provides only a "snapshot" of care, by a single observer, without observing any other care interactions throughout the day, although the WR is undoubtedly the key interaction between the doctor and the patient, other assessments did take place. However, the outcome of most, if not all, of these were captured via subsequent review of medical records and were factored into a number of identified errors.…”
Section: Discussionmentioning
confidence: 99%